2021
DOI: 10.21203/rs.3.rs-450002/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral health-related quality of life in patients with X-linked hypophosphatemia: a qualitative exploration

Abstract: Background. X-linked hypophosphatemia (XLH) is a rare, hereditary, and lifelong phosphate wasting disorder characterized by rickets in childhood and impaired teeth mineralization. In the oral cavity, spontaneous abscesses can often occur without any clinical signs of alteration of the causal tooth. The objective of our study was to evaluate the oral care pathway and the oral health-related quality of life (OHRQoL) of patients followed in an expert oral medicine department located within a Parisian hospital and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Dental conditions could also have been underreported, as dental treatments are typically performed by the participants' dentist, and their records may not have been available for the physician treating the participant's general XLH. Indeed, a survey by Nguyen et al noted that many participants did not receive adequate support for dental conditions and experienced a disorganized care pathway, which may have led to di culties in collection of patient data [27]. The aetiology of dental conditions in XLH is unclear, and the impact of treatment is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental conditions could also have been underreported, as dental treatments are typically performed by the participants' dentist, and their records may not have been available for the physician treating the participant's general XLH. Indeed, a survey by Nguyen et al noted that many participants did not receive adequate support for dental conditions and experienced a disorganized care pathway, which may have led to di culties in collection of patient data [27]. The aetiology of dental conditions in XLH is unclear, and the impact of treatment is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly consistent with the data published by Nguyen et al, who found that dental abscesses were a cause of intense pain, altered smile and problematic chewing -all contributing factors to the reduced quality of life of participants with XLH. This highlights the need for specialized care by dental experts aware of the role of XLH in dental conditions and for early intervention to reduce later complications [27].…”
Section: Discussionmentioning
confidence: 99%